Final Report on Assessment Instruments for a Prospective Payment System Appendices - Buchanan, Joan L. (RAND Corporation, 2004)
These appendices accompany a report that evaluates alternative assessment tools for use in a prospective payment system (PPS) for inpatient rehabilitation facilities. They include samples of study forms and instructions; descriptions of measures; recruitment and participation letters; characteristics of participating facilities; sample study newsletters; and sampling protocols.